Analisa Desain Chassis Mobil Listrik Satu Penumpang Dengan Finite Elemen Methode - Awalludin, Fachrul; Ardika, Rizki Dwi; Winangun, Kuntang; Arifin, Rizal; Fadelan, Fadelan; Munaji, Munaji; Winardi, Yoyok (AutoMech : Jurnal Teknik Mesin, 2025)
This Research In analyzing the design of a single-passenger electric vehicle chassis using the Finite Element Method (FEM) with Autodesk Inventor Professional 2021 (Student Version), the chassis plays a critical role in reinforcing the vehicle's frame to withstand greater loads. The design was modeled in Autodesk Inventor and analyzed using FEM to assess stress distribution, deformation, and the safety factor. The objective of the analysis was to ensure optimal strength, stiffness, and weight efficiency. The results showed a reduction in chassis weight from 15.726 kg to 12.517 kg using the same material, stainless steel type 201, without significantly compromising structural strength. Overall, the study demonstrates that the chassis design has been well-optimized in terms of strength and weight efficiency. Despite some areas exhibiting more pronounced deformation, the chassis remains safe for use.Keywords: Chassis, Finite Element Methode, Autodesk Inventor, Stainless Steel 201, Design Analysis